2005
DOI: 10.1007/s10493-005-1666-z
|View full text |Cite
|
Sign up to set email alerts
|

S-isorobinal as the female sex pheromone from an alarm pheromone emitting mite, Rhizoglyphus setosus

Abstract: The female sex pheromone of Rhizoglyphus setosus Manson (Astigmata: Acaridae) was identified as S-isorobinal (4S-4-isopropenyl-3-oxo-1-cyclohexene-1-carboxyaldehyde), which stimulated males sexually and enhanced the frequency of the male's tapping and mounting behavior. Although the female hexane extract indicated no sign of sex pheromone activity against tested males, possibly due to the presence of the alarm pheromone neryl formate, an SiO2 column fraction containing isorobinal elicited sex pheromone activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…"oki", 2) without any biological activity, and was then re-identified as the sex pheromone of R. setosus, together with its S stereochemistry. 4) In this study, the stereochemistry of 1 present in each corresponding extract of two species, the unidentified Rhizoglyohus sp. "oki" and Rhizoglyohus sp.…”
Section: Determination Of Stereochemistry and Its Distribution Among mentioning
confidence: 96%
See 1 more Smart Citation
“…"oki", 2) without any biological activity, and was then re-identified as the sex pheromone of R. setosus, together with its S stereochemistry. 4) In this study, the stereochemistry of 1 present in each corresponding extract of two species, the unidentified Rhizoglyohus sp. "oki" and Rhizoglyohus sp.…”
Section: Determination Of Stereochemistry and Its Distribution Among mentioning
confidence: 96%
“…3) (S)-Isomer of 1 has been demonstrated as the female sex pheromone of the related mite, Rhizoglyphus setosus (Acari: Acaridae), 4) using both enantiomers of 1 prepared by a group from Tohoku University 5) and also by us. Herein we report the syntheses of both enantiomers to determine the stereochemistry and the natural distribution of 1 among Astigmata.…”
Section: Introductionmentioning
confidence: 99%
“…Active components of these pheromones are secreted from a pair of opisthonotal glands present in each species (Kuwahara et al, 1979 and1980;Mizoguchi et al, 2003). Chemical structures of the pheromones so far known are classified into three groups; 1) monoterpenes, 2) aromatics and 3) hydrocarbons (Kuwahara, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other than alarm pheromones, sex and aggregation pheromones are also present as the same gland components of Astigmata (Kuwahara et al, 1980;Mizoguchi et al, 2003), and it is reasonable to understand that each species can handle a kind of pheromone function within the three. Recently, it has been realized that a species of mites can manipulate at least two kinds of pheromones (Kuwahara, 2001), such as found in Rhizoglyphus robini where a combination of the alarm and sex pheromones (neryl formate and α-acaridial, respectively) present in the same gland is manipulated to show each own function (Mizoguchi et al, 2003), and as found in Schwiebea elongata where neral functions not only as an alarm pheromone at a high dose but also as an attractant at a low dose, possibly an aggregation pheromone (Nishimura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation